KARAKTERISTIK, HAMBATAN-HAMBATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHA KECIL MENENGAH (Studi kasus UKM Batik Tulis Trusmi di Desa Trusmi Wetan dan Kulon Kecamatan Plered Kabupaten Cirebon) - Suripto Suripto; Iman Krismanto (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2020)
This study discusses the characteristics, constraints and factors of production of Trusmi written batik SMEs in Trusmi Wetan and Trusmi Kulon Villages, Plered District, Cirebon Regency. The objectives of this study are: (1) analyzing the characteristics of Trusmi handmade batik seen from business owners, the output/products produced and marketing, (2) analyzing the difficulties/obstacles experienced by Trusmi handmade batik UKM, (3) analyzing the influence of factors -factors of production against the amount of batik production Trusmi. This study uses statistical analysis tools both descriptive and inferential. Descriptive analysis is used to determine the characteristics, difficulties and obstacles experienced by SMEs in batik writing. Multiple linear regression is used to determine the effect of variable raw materials, wages, labour, education and business experience on the amount of Trusmi written batik production in Trusmi Wetan and Kulon villages, Plered District, Cirebon Regency. The results showed that (1) the characteristics of owners/entrepreneurs of Batik Tulis Trusmi as many as 15 (50%) craftsmen started their business background from generation to generation/inheritance and as many as 15 (50%) the rest were independent business backgrounds. The level of craftsman education is dominated by high school and the average age of the craftsman is 51 years. Products produced by craftsmen in the form of hem/shirt, sarong, shawl and marimbist in their marketing crafters supply several showrooms in Trusmi and are sent to several regions, (2) batik artisans experience difficulties and obstacles in terms of capital, raw materials and human resources, (3 ) multiple linear regression using individual test (t-test) shows that raw materials and wages have a positive and significant effect on the amount of batik production, while the amount of labour, education and business experience does not affectt